2018
DOI: 10.1007/s00167-018-4916-4
|View full text |Cite
|
Sign up to set email alerts
|

Low rates of patients meeting return to sport criteria 9 months after anterior cruciate ligament reconstruction: a prospective longitudinal study

Abstract: PurposeThe purpose of the current prospective study was to assess the changes over time in patients tested at 6 months and 9 months after anterior cruciate ligament reconstruction (ACLR) with a return to sport (RTS) test battery. It was hypothesized that more patients passed RTS criteria at 9 months compared to 6 months.MethodsSixty-two ACLR patients performed a test battery at an average of 6.5 ± 0.7 and 9.5 ± 0.9 months after ACLR. All patients underwent a standardized rehabilitation protocol. The test batte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
97
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 43 publications
(72 reference statements)
9
97
1
3
Order By: Relevance
“…Patient-report criteria were used in 26 (12%) of the 209 studies and included the subcategories patient-reported outcome measures (PROMs), subjective statements and reports of pain (table 7). Six studies [37][38][39][40][41][42] (3%) used one outcome measure, and two studies 43 44 (1%) used two measures. One study 45 reported pain and subjective reports as RTS criteria and one study 40 used PROMs and subjective statements as RTS criteria.…”
Section: Patient-report (Contextual Factors)mentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-report criteria were used in 26 (12%) of the 209 studies and included the subcategories patient-reported outcome measures (PROMs), subjective statements and reports of pain (table 7). Six studies [37][38][39][40][41][42] (3%) used one outcome measure, and two studies 43 44 (1%) used two measures. One study 45 reported pain and subjective reports as RTS criteria and one study 40 used PROMs and subjective statements as RTS criteria.…”
Section: Patient-report (Contextual Factors)mentioning
confidence: 99%
“…In at least one recent study, a movement quality test (Landing Error Scoring System) was used as part of a RTS test battery along with the International Knee Documentation Committee subjective knee form and the ACL-Return to Sport after Injury scale. 42 All of the studies included in our scoping review were focused on the RTS element of the RTS continuum (figure 4). 9 However, for many athletes, return to performance-the third element of the RTS continuum-is their primary focus.…”
Section: What Are the New Findingsmentioning
confidence: 99%
“…35 Among young active ACLR individuals, less than half may fulfill a ≥90% LSI criterion for quadriceps strength. 7,36,37 Within ACLinjured adults, Welling et al 38 reported that only 13 patients out of 62 (21%) reached ≥90% LSI criterion for quadriceps strength 9 months after ACLR. In a study by Cristiani et al 8 where 4093 patients were assessed 6 months after ACLR, 36% and 47% reached the ≥90% LSI criterion for quadriceps and hamstring strength, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Results from only hop performance can be insufficient as RTS criteria. Furthermore, as demands increase by adding more MF tests, the passing rate (the proportion of patients reaching a given cutoff value) is reduced [16][17][18]. It is, however, unknown if adding an assessment of psychological outcome to MF tests will result in different passing rates, resulting in a better foundation for decisions on RTS.…”
Section: Introductionmentioning
confidence: 99%